Analysis of Factors Affecting Edamame Exports to Timor Leste: Analisis Faktor-Faktor yang Mempengaruhi Ekspor Edamame ke Timor Leste - Yolani Ika Saputri; Fatchur Rozci; Markus Patiung; Nugrahini Susantinah Wisnujati (Jurnal Ilmiah Manajemen Agribisnis, 2026)
This study analyzes the factors affecting the export volume of Indonesian edamame to Timor-Leste during the 2013–2022 period. The independent variables include Indonesian edamame production volume, Timor-Leste's GDP, international edamame prices, and the rupiah-to-US dollar exchange rate. Secondary time-series data were obtained from TradeMap, the World Bank, FAO, and Bank Indonesia, and analyzed using multiple linear regression with SPSS version 20. The partial test results show that production volume, Timor-Leste's GDP, and international prices do not significantly affect export volume. In contrast, the exchange rate has a positive and significant effect (at α = 10%), where rupiah depreciation enhances product competitiveness, thereby increasing exports. Simultaneously, all four variables explain 80.4% of the variation in export volume. These findings indicate that exchange rate stabilization policies and market diversification strategies need to be strengthened to improve edamame export performance to Timor-Leste.